THE DEVELOPMENT OF READING LITERACY AMONG FUTURE NURSES (Scientific journal of the Fergana State University, 2024)
This study examines the effectiveness of reading through rhythmics for prospective nurses who had difficulty recognizing medical vocabulary. The study focused on the development of medical vocabulary reading skills using rhythmic tempo. The materials comprised 50 of the most famous poems on the subject of human body anatomy according to the training course. The aim was to work out phonological accompaniment when reading, consolidate knowledge about the anatomy of the human body and streamline the reading process using rhythmic tempo. Compared with medical students (Faculty of Pediatrics) who accidentally fell into the control group, those who read poorly (students of the Faculty of Nursing) in the study conditions showed significant improvements in standardized indicators of independent reading, direct word recognition and reading comprehension based on text after an experiment with a period of a whole semester. During the experiment, future nurses also showed great improvements in the development of word recognition compared to medical students of the pediatric faculty, taking into account the effectiveness of recognition of clinical vocabulary. The results indicate that the introduction of a tempo rhythm into the reading process, using the example of reading poetry, is an effective way to raise the low level of reading comprehension among medical professionals, especially nurses.